2022
DOI: 10.2478/enr-2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of glutamine deprivation on the expression of MEIS3, SPAG4, LHX1, LHX2, and LHX6 genes in ERN1 knockdown U87 glioma cells

Abstract: Objective. The aim of the current study was to investigate the expression of genes encoded homeobox proteins such as MEIS3 (Meis homeobox 3), SPAG4 (sperm associated antigen 4), LHX1 (LIM homeobox 1), LHX2, and LHX6 in U87 glioma cells in response to glutamine deprivation in control glioma cells and cells with knockdown of ERN1 (endoplasmic reticulum to nucleus signaling 1), the major pathway of the endoplasmic reticulum stress signaling, for evaluation of a possible dependence on the expression of these impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…These results clearly demonstrated that the expression of PDHA1, PDHB, DLAT, and DLD genes is controlled by glutamine supply and that this control is ER stress dependent particularly through ERN1 signaling. This is in accordance with the data our previous studies (Minchenko et al , 2020(Minchenko et al , 2021Tsymbal et al 2016;Krasnytska et al 2022) as well as studies of other authors (Drogat et al 2007). The changes in PDHA1 and PDHB genes expression under glutamine deprivation are in agreement with data of Yetkin-Arik et al (2019) indicating that silencing of PDHA1 expression prevents the proliferation of HUVECs, because this enzyme of PDH complex is a crucial regulator of pyruvate metabolic pathways (Zaher et al 2021).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results clearly demonstrated that the expression of PDHA1, PDHB, DLAT, and DLD genes is controlled by glutamine supply and that this control is ER stress dependent particularly through ERN1 signaling. This is in accordance with the data our previous studies (Minchenko et al , 2020(Minchenko et al , 2021Tsymbal et al 2016;Krasnytska et al 2022) as well as studies of other authors (Drogat et al 2007). The changes in PDHA1 and PDHB genes expression under glutamine deprivation are in agreement with data of Yetkin-Arik et al (2019) indicating that silencing of PDHA1 expression prevents the proliferation of HUVECs, because this enzyme of PDH complex is a crucial regulator of pyruvate metabolic pathways (Zaher et al 2021).…”
Section: Discussionsupporting
confidence: 94%
“…Glutamine and glucose supply as well as endoplasmic reticulum (ER) stress are very important and complementary factors for the tumor growth. This is also confirmed by the fact that inhibition of endoplasmic reticulum to nucleus signaling 1 (ERN1)/inositol requiring enzyme 1 (IRE1) modifies the effect of glutamine and glucose deprivations on the expression of numerous genes (Minchenko et al , 2015a(Minchenko et al , 2020(Minchenko et al , 2021Tsymbal et al 2016Tsymbal et al , 2020Riabovol et al 2019;Krasnytska et al 2022). Bioinformatics profiling identifies a glucose-related risk signature for the malignancy of glioma (Zhao et al 2017).…”
mentioning
confidence: 81%
“…Our study also found that INTS6 was a favorable prognosis gene for OV. SPAG4, was also defined as a novel potential cancer marker 55 , however, the level of SPAG4 expression was decreased in glioma cells treated by glutamine deprivation 56 . ZNF316 has been identified as a transcription factor, although its specific role in OV remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Hirschsprung's disease, a hereditary disorder with congenital megacolon as its primary symptom, is caused by MEIS3 deficiency and affects children and newborns [24]. Although there have been reports about the role of MEIS3 in hepatocellular carcinoma and glioma, whether and how MEIS3 participates in the progression of gut tumors is currently unknown [25,26].…”
Section: Introductionmentioning
confidence: 99%